Effect of transverse magnetic field on wake dynamics and heat transfer through a porous circular cylinder. Issue 8 (19th August 2022) - Kumar, Chandan; Chatterjee, Dipankar; Mondal, Bittagopal
Abstract: A two‐dimensional numerical simulation using the commercial computational fluid dynamics package ANSYS Fluent 15.0 is performed to investigate the effect of a transverse magnetic field on the wake dynamics around a heated porous circular cylinder. The study is conducted considering a Newtonian, incompressible, and electrically conductive fluid with constant properties for the low Reynolds number laminar regime. In the range of Reynolds number ( Re = 10–40), recirculating vortices are observed to penetrate (or detach) into (from) the porous cylinder surface depending on the Darcy number, Da (10 −6 to 10 −2 ). The effect of the magnetic field parameter (Hartmann number) Ha (0–10) on the detachment and penetration characteristics of a porous cylinder is reported for the first time. A steady separated flow behind the cylinder turns into an attached flow at a critical magnetic field strength. Accordingly, the critical Hartmann number ( Ha cr ) is estimated for the complete suppression of the flow separation behind the porous cylinder. Ha cr is found to decrease with an increase in Da and a decrease in Re . The wake behind the cylinder is also found to be detached from the cylinder surface at a particular value of the magnetic field strength termed as the detachment Hartmann number ( Ha d ). Ha d also decreased with an increase in Da and decrease of Re. In addition, the effect of Ha on the separation angle, recirculation length, detachment length, and drag coefficient is also discussed. Furthermore, the effect of the magnetic field on the forced convective heat transfer characteristics is also studied considering various fluids (Prandtl number, Pr = 0.02, 0.71, and 7) past the circular permeable cylinder. At a particular Pr, the heat transfer rate is almost invariant for low permeability, whereas it increases significantly at higher permeability with an applied magnetic field. The rate of heat transfer increases with the Prandtl number for all Hartmann and Darcy numbers. Finally, a correlation is developed to predict the average heat transfer as a function of Re, Pr, Da, and Ha .